Lesotho Social Protection Programs and Systems Review - World Bank (World Bank, Washington, DC, 2021)
Lesotho, a high-altitude, landlocked country of 2.1 million people encircled by South Africa, has made gains in poverty reduction over the last decade but challenges of shared prosperity remain. The country has made significant investments in developing social protection programs as part of the Government’s commitment to protecting vulnerable groups. In sum, while several social assistance programs in Lesotho are found to be effective, whether measured by impact or spending effectiveness, spending on social protection is very high and cost-effectiveness varies.